Professional Language Studing by Students-designers as an Important Communicative Method - Momotova, Lilia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The study was conducted in groups of 1-2 courses. Professional anguage is digested through professional terminology learning, different ways of working with the material are provided for this (tables, clusters, classification, discussion, the interpretation of the Glossary through a picture and other methods). Necessary information allowing to penetrate deeper into the subject and to form design concept more precisely is acquired. Professional language learning forms the world outlook, it enables students to study special disciplines consciously and allows them to reach a new stage of development of professional qualities and intelligence. Analysis of terminology assimilation shows that professional language learning is aimed at intensifying learning and cognitive activity. Development of cognitive interest gives a new content to studying, therefore professional language teaching is the most impotent technique of human communication and a means of forming thoughts.The aim of the research is substantiating the need of professional language studying by students-designers and acquainting the reader with the methods of work that contribute to the formation of the common professional culture and they are a step towards the realization of the task of combining education and the cognitive function of the training.